Implications of the Clean Air Act Amendments for the Northeast - Belanger, Joseph (Maine Policy Review, 1993)
The Clean Air Acts Amendments (CAA) of 1990 continue to affect public policy at the federal, state and local levels of government. At the PURE ’93 Conference last January, "Alternatives to Traditional Regulation," one panel explored the implications of the CAA on the Northeast. Joseph A. Belanger of the Connecticut Department of Environmental Protection provided this assessment of Title 1 of the CAA, particularly with respect to ozone attainment requirements.
Keywords: Clean Air Act; Northeast